2023
DOI: 10.1177/20552076231173568
|View full text |Cite
|
Sign up to set email alerts
|

Investigating information needs and preferences regarding digital mental health services among medical and psychology students in Germany: A qualitative study

Abstract: Background Since 2020, physicians and psychotherapists in Germany can prescribe digital mental health services (dMHSs). However, even future healthcare professionals (HCPs), such as medical and psychology students, remain reluctant to use dMHSs, although they are a risk group for mental health issues themselves. Reasons include scepticism and lacking awareness of dMHSs, which can be addressed by acceptance-facilitating interventions (AFIs) such as information strategies. To date, though, little is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…Seventh, due to the relatively old data, preferences and attitudes may have changed over time, as efforts for the digitalization of the health care sector have sharply increased, for example, due to the COVID-19 pandemic. However, a more recent qualitative study on digital mental health services showed that German students only have little experience with this kind of services ( 62 ). Eighth, the 12-month mental disorders were solely based on self-reported DSM-IV criteria which may have led to inflated prevalences due to self-selection and recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Seventh, due to the relatively old data, preferences and attitudes may have changed over time, as efforts for the digitalization of the health care sector have sharply increased, for example, due to the COVID-19 pandemic. However, a more recent qualitative study on digital mental health services showed that German students only have little experience with this kind of services ( 62 ). Eighth, the 12-month mental disorders were solely based on self-reported DSM-IV criteria which may have led to inflated prevalences due to self-selection and recall bias.…”
Section: Discussionmentioning
confidence: 99%